THE EFFECT OF PH OF NUTMEG JUICE ON REDUCING SUGAR CONTENT AND HARD CANDY TEXTURE - Judith Henny Mandei; Alim Mahawan Nuryadi (Balai Riset Dan Standardisasi Industri Manado, 2019)
Research on the effect of pH of nutmeg on reducing sugar content and hard candy texture has been carried out. The aim of the study was to look at the effect of pH on the reducing sugar content and texture of nutmeg candy, and to obtain hard nutmeg candy that meets the requirements of SNI 3547.1-2008 specifically the reducing sugar content. The study used a randomized block design, which was treated as pH of nutmeg juice: pH 5, pH 6, and pH 7. The treatment group was the type of addition of nutmeg juice, namely: nutmeg juice; nutmeg juice + nutmeg oil 0.5%; nutmeg juice + 0.5% dried nutmeg meat pieces; and nutmeg juice + nutmeg oil and 0.5% dried nutmeg pieces. The main observation was carried out on the reducing sugar levels and the texture of nutmeg candy especially stickiness. Quality testing includes water content, sucrose levels, ash content, appearance/color, taste and odor. The results were statistically analyzed by the analysis of variance to determine significant differences between the samples using the software Minitab 17 (specifically the reducing sugar parameters). The pH of nutmeg juice affects the reducing sugar levels and the texture of nutmeg candy. Nutmeg candy made from nutmeg juice with pH 5 and 6 produces nutmeg candy with reduced sugar content of 3.29% and 3.18% (fulfilling the requirements for reducing sugar quality of SNI SNI 3547.1-2008 hard candy), with a non-sticky texture and easily bitten. The type of addition of nutmeg juice does not affect the reducing sugar content and texture of nutmeg candy.Keywords: Hard candy, nutmeg juice, pH, texture.